2013
DOI: 10.1038/bjc.2012.553
|View full text |Cite
|
Sign up to set email alerts
|

Altered TUBB3 expression contributes to the epothilone response of mitotic cells

Abstract: Background:Epothilones are a novel group of microtubule (mt) targeting cancer drugs that bind to the β-subunit of the αβ-tubulin dimer. Epothilones inhibit cell proliferation and induce cell death by interfering with the normal mt function. In this study, we examined the consequences of altered expression of human β-tubulin isotypes in terms of the epothilone drug response in human lung and breast cancer cell lines.Methods:The β-tubulin isotypes TUBB2A–C, TUBB3 and TUBB were silenced or overexpressed in A549, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 31 publications
0
37
1
Order By: Relevance
“…Moreover, the exogenous protein appears to be incorporated in microtubules, including those of the midbody (Supplementary Figure S2C), as previously reported. 41 The overexpression (Figure 4a) or knockdown ( Figure 4b) of TUBB3 had no effect on the basal rate of cytokinesis failure. The overexpression of TUBB3 in CIT-K-depleted HeLa cells significantly increased the ratio of binucleated cells generated within the observation time (Figure 4a).…”
Section: Resultsmentioning
confidence: 93%
“…Moreover, the exogenous protein appears to be incorporated in microtubules, including those of the midbody (Supplementary Figure S2C), as previously reported. 41 The overexpression (Figure 4a) or knockdown ( Figure 4b) of TUBB3 had no effect on the basal rate of cytokinesis failure. The overexpression of TUBB3 in CIT-K-depleted HeLa cells significantly increased the ratio of binucleated cells generated within the observation time (Figure 4a).…”
Section: Resultsmentioning
confidence: 93%
“…In addition, other microtubule-targeted drugs including estramustine, vincristine, and vinorelbine interact more weakly with βIII-tubulin than with other β-tubulin isotypes in vitro [32][33][34][35]. Epothilones, from which ixabepilone was derived, are also more effective when βIII-tubulin levels are reduced [15]. Differences in amino acid sequences of βIII-tubulin as compared to other β-tubulin isotypes [36] are likely responsible for the differences.…”
Section: Effects Of βIii-tubulin and Ixabepilone On Microtubule Dynammentioning
confidence: 95%
“…Drug binding and suppression of microtubule dynamic instability also impair many interphase functions of microtubules including migration, intracellular trafficking, and cell secretion [11][12][13]. Several studies have briefly reported some of ixabepilone's properties in cells [14,15] and in vitro [7][8][9], but there has been no full elucidation of its mechanism of action including its response to altered tubulin isotype expression.…”
Section: Introductionmentioning
confidence: 99%
“…Epothilones from the myxobacterium Sorangium cellulosum are potential anticancer drugs that act as microtubule disrupters, similar to taxanes 164 . Several epothilone analogues are currently undergoing clinical trials: patupilone (also known as EPO-906 or epothilone B) has been through Phase III trials in the United States and Phase III trials are ongoing in the United Kingdom, Spain, and…”
Section: Applyingmentioning
confidence: 99%